Drought Tolerance and Competition in Eastern Redcedar (Juniperus virginiana) Encroachment of the Oak-Dominated Cross Timbers - Torquato, Patricia R.; Zou, Chris B.; Adhikari, Arjun; Adams, Henry D.; Will, Rodney E. (Frontiers in Plant Science, 2020)
On the dry, western edge of the eastern deciduous forest of the USA (Cross Timbers), the drought-tolerant, evergreen eastern redcedar (Juniperus virginiana) is encroaching into post oak- (Quercus stellata) dominated woodlands. The overall goal of this study was to examine whether the drought tolerance strategies of eastern redcedar provide it a competitive advantage over post oak and whether this is a key attribute facilitating its successful establishment in the Cross Timbers. Specifically, we assessed xylem water potential and leaf gas exchange of these two species growing in single-species stands and in a mixed-species stand. We found that both species exhibit a similar degree of isohydry and close their stomates to the same extent in response to declining xylem water potentials. Both species had similar relative reductions in gas exchange in response to drought, despite differences in xylem anatomy. However, post oak had leaf-level gas exchange rates approximately 5× greater than eastern redcedar during periods of high moisture availability. Therefore, it did not appear that eastern redcedar encroachment into an oak-dominated forest is facilitated by growing season differences in carbon gain, although evergreen eastern redcedar can conduct gas exchange year-round when conditions are favorable while post oak is deciduous. We found that volumetric soil water content (0-45 cm) was lower in the pure eastern redcedar stand than the mixed-species or pure post oak stand which may indicate that eastern redcedar may experience favorable soil moisture conditions when encroaching into open oak woodlands. Moreover, water potentials in eastern redcedar tended to be more negative in pure stands compared to the mixed stand. Our results suggest the two species may be using water from different depths, reducing competition. Overall, our findings indicate that eastern redcedar encroachment into formerly oak-dominated Cross Timbers forests likely will continue under moderate drought, in the absence of fire, with consequences for water budgets, carbon cycling, grazing forage, wildlife habitat, and wildfire risk.